Description of the previously unknown sexes in four West African Lycaenidae (Lepidoptera) with new data on their distribution - Sáfián, Szabolcs (Zootaxa, 2020)
Several new butterfly species in the family Lycaenidae were found during recent field surveys in Liberia. Amongst these, quite a few were collected as singletons or in small series, represented by only one of the sexes. This paper describes and illustrates the previously unknown sexes of four of those species which were subsequently found, adding new locality records to their known distribution.